Selected Topics in Performance Evaluation and Benchmarking 4th TPC Technology Conference, TPCTC 2012, Istanbul, Turkey, August 27, 2012, Revised Selected Papers - Nambiar, Raghunath; Poess, Meikel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 4th TPC Technology Conference, TPCTC 2012, held in Istanbul, Turkey, in August 2012. It contains 10 selected peer-reviewed papers, 2 invited talks, a report from the TPC Public Relations Committee, and a report from the workshop on Big Data Benchmarking, WBDB 2012. The papers present novel ideas and methodologies in performance evaluation, measurement, and characterization.
TPC Benchmark Roadmap 2012 -- Incorporating Recovery from Failures into a Data Integration Benchmark -- Two Firsts for the TPC: A Benchmark to Characterize Databases Virtualized in the Cloud, and a Publicly-Available, Complete End-to-End Reference Kit -- Adding a Temporal Dimension to the TPC-H Benchmark -- Performance Per Watt - Benchmarking Ways to Get More for Less -- Revisiting ETL Benchmarking: The Case for Hybrid Flows -- MulTe: A Multi-Tenancy Database Benchmark Framework -- BDMS Performance Evaluation: Practices, Pitfalls, and Possibilities -- Data Historians in the Data Management Landscape -- Scalable Generation of Synthetic GPS Traces with Real-Life Data Characteristics -- S3G2: A Scalable Structure-Correlated Social Graph Generator -- Benchmarking in the Cloud: What It Should, Can, and Cannot Be -- Characterizing Cloud Performance with TPC Benchmarks -- Setting the Direction for Big Data Benchmark Standards.
Keywords: Computer science; Computer system performance; Software engineering; Database management; Information systems; Computer Science; System Performance and Evaluation; Database Management; Software Engineering; Computer Appl. in Administrative Data Processing